INVESTIGATING THE ASSOCIATION BETWEEN TRADITIONAL CHINESE MEDICINE SYNDROMES AND DISEASE STAGES IN LUNG CANCER PATIENTS AT HO CHI MINH CITY ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of Traditional Chinese Medicine (TCM) syndromes and their association with TNM stages in lung cancer patients at Ho Chi Minh City Oncology Hospital.Methods: A cross-sectional study was conducted on 392 patients (Dec 2024 – May 2025).  TNM stages and TCM syndromes were collected via direct interviews using a standardized questionnaire based on the 2023 CACM guidelines and expert consensus, and medical records. Data were analyzed using multivariate logistic regression, controlling for age, sex, BMI, and smoking history.Results: Qi deficiency (51.3%), Yin deficiency (35.5%), and Phlegm-dampness (27.0%). Multivariate analysis revealed no significant association between these three syndromes and TNM stages (p > 0.05). Notably, a history of smoking was identified as an independent risk factor, increasing the odds of Blood stasis by 1.84 times (aOR = 1.84, 95% CI: 1.04 – 3.31, p = 0.039).Conclusion: Qi deficiency, Yin deficiency, and Phlegm-dampness serve as foundational syndromes present throughout the disease process, independent of TNM staging. Smoking is a significant independent factor associated with Blood stasis.
Keywords: Lung cancer, TCM syndromes, TNM staging.